Transnational Entrepreneurs: Implications of the dual background on opportunity recognition - Radulov,Kalin; Shymanskyi,Oleg (2014)
Transnational entrepreneurs are migrant business owners, traveling abroad for business purposes and engaged in business activities, based on ties to a foreign country. Operating in two countries exposes the entrepreneur to more sources of information and can increase the ability of the entrepreneur to make connections and discover opportunities. Using dual habitus and theory of practice as the main theoretical framework, this paper explores the sources of information of transnational entrepreneurs, and how they are influenced by their unique position of being embedded in two countries at the same time. A case study on transnational entrepreneurs in Skåne is conducted. The data for the study is obtained through the use of general, semi-structured interviews with entrepreneurs, fitting the profile. The critical incidents, leading to opportunity recognition are identified. The findings reveal a clear link between the entrepreneur's transnational background and the recognised opportunity. Furthermore, the results suggest that the main sources of information used to identify opportunities are knowledge corridors and social ties. A link between an individual's transnationalism and perceived competitive advantage is established. The conclusion underlines the value of international experiences and suggests a link between transnationalism and enhanced creativity. Future and practical implications are suggested.
Keywords: entrepreneurship; transnational entrepreneurship; transnationalism; dual habitus; opportunity recognition; knowledge corridors; social ties; critical incidents; competitive advantage; Sweden; Skåne.